PANDANGAN GENERASI Z TERHADAP PENGGUNAAN DOPING DEMI PRESTASI OLAHRAGA - Nimrot Manalu; Ariel Ginting; Della Wiyanti; Sasta Syehan Yadaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine Generation Z's views on the use of doping in sports to achieve achievement. The study used a quantitative approach with a descriptive survey design. The sample consisted of 120 Generation Z individuals aged 17–25 years old selected through purposive sampling techniques from universities and high schools in Medan City. The instrument used was a Likert-scale questionnaire that had been validated by experts and tested for reliability using the Cronbach's Alpha method. Data analysis was conducted using descriptive statistics and the chi-square test. The results showed that 82% of Generation Z respondents viewed doping as a form of cheating and a violation of sportsmanship values. However, 61% also acknowledged that high competitive pressure was the main motivating factor for athletes to use doping. Furthermore, 74% of respondents considered anti-doping education in schools and on social media to be inadequate. It was concluded that Generation Z has a tendency to have a negative view of doping use.